A study of oligothiophene–acceptor dyes in p-type dye-sensitized solar cells. Issue 22 (12th February 2016) - Sheibani, Esmaeil; Zhang, Lei; Liu, Peng; Xu, Bo; Mijangos, Edgar; Boschloo, Gerrit; Hagfeldt, Anders; Hammarström, Leif; Kloo, Lars; Tian, Haining
Abstract : Two new dyes, E1 andE2, equipped with triphenylamine as the electron donor, oligothiophene as the linker and different electron acceptor groups, have been designed and synthesized as photosensitizers for p-type dye-sensitized solar cells (p-DSCs). Abstract : Two new dyes, E1 andE2, equipped with triphenylamine as the electron donor, oligothiophene as the linker and different electron acceptor groups, have been designed and synthesized as photosensitizers for p-type dye-sensitized solar cells (p-DSCs). A systematic study of the effect of molecular structures on the observed photophysical properties, the electron/hole recombination process, the overall performance and the interfacial charge separation was carried out. Transient absorption spectroscopy (TAS) shows that theE1 dye with a napthoilene-1, 2-benzimidazole (NBI) unit as the acceptor has a longer lifetime in the reduced state than theE2 dye with a malononitrile subunit on the NiO surface.